Dopamine enhances willingness to exert effort for reward in Parkinson's disease. (August 2015) - Chong, Trevor T.-J.; Bonnelle, Valerie; Manohar, Sanjay; Veromann, Kai-Riin; Muhammed, Kinan; Tofaris, George K.; Hu, Michele; Husain, Masud
Abstract: Parkinson's disease (PD) is traditionally conceptualised as a disorder of movement, but recent data suggest that motivational deficits may be more pervasive than previously thought. Here, we ask whether subclinical deficits in incentivised decision-making are present in PD and, if so, whether dopaminergic therapy ameliorates such deficits. We devised a novel paradigm in which participants decided whether they were willing to squeeze a hand-held dynamometer at varying levels of force for different magnitudes of reward. For each participant, we estimated the effort level at which the probability of accepting a reward was 50% – the effort 'indifference point'. Patients with PD ( N = 26) were tested ON and OFF their usual dopaminergic medication, and their performance compared to those of age-matched controls ( N = 26). No participant was clinically apathetic as defined by the Lille Apathy Rating Scale (LARS). Our data show that, regardless of medication status, patients with PD chose to engage less effort than controls for the lowest reward. Overall, however, dopamine had a motivating effect on participants' choice behaviour – patients with PD chose to invest more effort for a given reward when they were in the ON relative to OFF dopamine state. Importantly, this effect could not be attributed to motor facilitation. We conclude that deficits in incentivised decision-making are present in PD even in the absence of a clinical syndrome of apathy when rewards are low, but that dopamine acts to eliminate motivational deficits by promoting the allocation of effort.